Implementation Of Advanced Control Laws On A Laboratory-Scale Three-Tank System - Bamimore, Ayorinde; Ogunba, Kolawole S.; Ogunleye, Musbau A.; Taiwo, Olufemi; Osunleke, A.S.; King, R. (Ife Journal of Technology, 2012)
A laboratory-scale three-tank system for Control Engineering Education has been installed at the Process System Engineering Laboratory of Obafemi Awolowo University, Ile-Ife, Nigeria. This study gives a description of the physical features of the three-tank system and the mathematical description of the dynamics of the system. Subsequently, the design and implementation of controllers using five popular advanced control laws are demonstrated. The performance of the designed control laws is displayed in set-point simulations using MATLAB and SIMULINK. The designs are then implemented on the physical system using the Real-Time Interface. The similarities observed between the experimental and simulation results show the effectiveness of the control systems and the usefulness of the set-up in demonstrating the practical relevance of advanced control laws.